MENUMBUHKAN KEPUASAN KERJA MELALUI INOVASI KOLEKTIF: PENGARUH IKLIM ORGANISASI TERHADAP GURU - Agus Setyawanto (EDUSIANA: Jurnal Manajemen dan Pendidikan Islam, 2025)
This study explores the relationship between organizational climate, collective innovation, and teacher job satisfaction within a rapidly evolving educational landscape. As teaching strategies and technologies evolve, promoting collaboration and innovation among teachers is crucial for adapting and improving the learning environment. The results show that collective innovation fully mediates the connection between organizational climate defined by teacher-student relationships, collaborative culture, and working atmosphere and teacher job satisfaction. Statistical analysis reveals significant positive correlations between the variables, with collective innovation having the strongest mediating effect (β = 0.419, p < 0.001). Teacher-student relationships were found to have the greatest impact on job satisfaction, followed by the working atmosphere and collaborative culture. The structural model showed a good fit with the data (CFI = 0.951; RMSEA = 0.059). This study underscores the importance of fostering an environment that supports collective innovation to enhance teacher well-being.